An interpretation of the conflict by the shortage in water service during 2014 in Barva de Heredia, Costa Rica - Montero, Diego (2016)
This article seeks to study the case of the conflict by the shortage in water service that was generated in Barva de Heredia during 2014. The first objective is to describe some of the most notable events of this conflict, in order to show the main features that acquired the dispute; later, as a second objective, set an analysis of the facts, focusing attention on the community organization that was created in the midst of the problem. For this, participant observation, news from newspaper, television reports as well as information, images and videos that were posted on the page of movement’s Facebook and website YouTube, were used.Thus, the approach that tries to defend is, in order to understand why the conflict between the community actors and municipal authorities did emerged, it is necessary to exceed its most immediate cause which was the cuts in water supply, paying attention to other political, historical and socio-cultural variables.